Long-term records (1781-2013) of European eel (Anguilla anguilla L.) production in the Comacchio Lagoon (Italy): Evaluation of local and global factors as causes of the population collapse - ASCHONITIS, Vasileios; CASTALDELLI, Giuseppe; LANZONI, Mattia; ROSSI, Remigio; Kennedy, Clive; FANO, Elisa Anna (Aquatic Conservation: Marine and Freshwater Ecosystems, 2017)
Several eel species have undergone extensive declines at both local and global level. The aim of this study was to identify the reasons for the collapse of the European eel (Anguilla anguilla) stock in an important area for biodiversity conservation (Comacchio Lagoon, Italy), in order to support the development of eel conservation plans. The records of silver eel catches from Comacchio describe the total migratory population and cover the period 1781-2013. The data are accompanied by information related to habitat loss and other local factors. The role of local factors on the decline of the local stock was investigated, while additional information from the literature was also used to discuss the effects of global factors (including glass eel harvest for aquaculture, climate-oceanographic changes, habitat loss, pollution and parasitism) on the three eel species A. anguilla, Anguilla japonica and Anguilla rostrata. The records from Comacchio provided significant information about the effects of local factors on the local eel populations in the past. However, the current population collapse, which started in the 1970s, could not be explained by local factors. The literature on global factors suggests that the three eel species are under combined threat from various factors. The correlations between European aquaculture production data compared with the Comacchio yields and published data from other European eel and glass eel fisheries were found to be highly significant. Aquaculture, which depends entirely on wild-caught glass eels, seems to play a key role in the decline of natural stocks. Conservative estimates using FAO data showed that the current numbers of glass eels needed to support aquaculture production in Europe and Asia exceeds 2 × 109 specimens. This requirement, largely supplied by A. anguilla glass eels, can explain the decline of eel populations since the glass eel trade has been expanded at an international level.